The Presidents' Wives : the Office of the First Lady in US Politics. - Watson, Robert P. (Lynne Rienner Publishers, 2014)
Robert Watson's groundbreaking study on the presidents' wives proved that the first lady can be an influential force in presidential politics and is a subject worthy of scholarly attention. Now, this fully revised second edition incorporates the first ladyships of Hillary Rodham Clinton, Laura Bush, and Michelle Obama in each chapter. The new edition also includes a decade-and-a-half of new research on public opinion, the growth and political development of the East Wing, and the issue of first lady character.